Gold Diggers in Paris - Enright, Ray; Barnes, George; Polito, Sol; Berkeley, Busby; Vallee, Rudy; Lane, Rosemary; Herbert, Hugh (Warner, 2010)
A French diplomat mistakes Rudy Vallee and his vaudeville show for a ballet company and invites them to Paris for a dance exposition. When the real ballerinas show up for the show, Vallee's group is kicked out, but they're determined to put their show on anyway. [www.dvdverdict.com]
Keywords: DVD-Video